FTIR and Electrical Properties of Cr Substituted Li0.5Fe2.5−xO4 Synthesized Using Sol-Gel Auto Combustion. (1st May 2022) - Patil, Swati D.; Mane, Sagar. M.; Kharade, Pravin M.; Thombare, Jagannath V.; Gaikwad, Rajendra S.; Tirpude, Manish P.; Shin, Jae Cheol; Dhasade, Shankar S.; Kim, Hyo Jin
Abstract : The highly desirable properties of lithium ferrite and various metal ion substituted lithium ferrite make it a useful material for many electronic and magnetic applications. This research used a simple sol-gel auto-combustion method for the synthesis of Cr substituted Li0.5 Fe2.5 O4 ferrite. Here, in the B-site, Fe 3+ ions were swapped by non-magnetic Cr 3+ ions at different concentrations. All the samples of Cr substituted Li0.5 Fe2.5 O4 were confirmed through X-ray diffraction patterns to have a single-phase spinel-type structure with cubic symmetry, which was thereafter confirmed by its refinement through Rietveld. An increase in the substitution of Cr 3+ instead of Fe 3+ ions in the spinel ferrite system results in an increased nanocrystalline size. The average crystallite size decreased from 30 nm to 10 nm with an increase in Cr 3+ content. Analogous particle size was evaluated through transmission electron microscopy (TEM) analysis. Fourier transform infrared spectroscopy (FTIR) provides an overview of the structural distortion of the lithium ferrite lattice with the substitution of Cr 3+ ions. The Semiconducting (NTCR) nature of the Cr substituted Li0.5 Fe2.5 O4 nanoparticles was confirmed through the temperature-dependent DC resistivity. The evaluated trend of the dielectric properties ( ε ′, ε ″, and tan δ ) strengthens the facts observed in the electrical conduction mechanism.